The influence of online education on pre-service teachers’ academic experiences at a higher education institution in the United Arab Emirates - Qiqieh, Sura; Dukmak, Samir (Frontiers in Education, 2024)
This study investigates the influence of online education on the academic experiences of 130 pre-service teachers attending the Postgraduate Diploma Program at Al Ain University in the UAE. It also explores the relationships between teachers' demographics and five academic experiences. A quantitative questionnaire consisting of five newly-developed scales was used for data collection. Teachers' demographics found not to impact effective teaching and learning, skill development, or satisfaction. Age and employment status found not to influence teachers' views of faculty online assessment and feedback or course organization and management. However, online course organization and management and faculty online assessment and feedback were significantly correlated with marital status as engagement and motivation with employment status was, but not with age or marital status. Effective teaching and learning, faculty assessment and feedback positively impacted teachers' engagement and motivation, while effective teaching and learning and course organization correlated with teachers' skill development and satisfaction.